MiR‐101‐loaded exosomes secreted by bone marrow mesenchymal stem cells requires the FBXW7/HIF1α/FOXP3 axis, facilitating osteogenic differentiation. Issue 6 (12th January 2021) - Li, Yanhong; Wang, Jing; Ma, Yanchao; Du, Wenjia; Feng, Kai; Wang, Shuanke
Abstract: Exosomes derived from mesenchymal stem cells (MSCs) have emerged as significant mediators of intercellular communication, with studies highlighting their role in the transmission of biological signals between cells. Dominant microRNA (miRNA)‐mediated translational repression of messenger RNAs has been extensively investigated in regard to its influence in orchestrating osteogenic differentiation. In the current study, we sought to ascertain the contributory role of miRNA‐101 (miR‐101) encapsulated in the process of bone marrow mesenchymal stem cell (BMSC)‐derived exosomes in osteogenic differentiation. Exosomes were initially extracted from BMSCs at Days 0, 3, 12, and 21 of osteogenic differentiation by ultracentrifugation. Artificial modulation of miR‐101 and FBXW7 (silencing and overexpression) were performed in the BMSCs to identify its effects on osteogenic factors, alkaline phosphatase activity, and osteogenic differentiation. Mechanistic exploration was performed to evaluate the binding affinity between miR‐101 and FBXW7, the FBXW7‐mediated HIF1α ubiquitination, and the HIF1α enrichment in the FOXP3 promoter region. Exosomes from MSCs in the late stage of osteogenic differentiation exhibited enhanced osteogenic differentiation. Upregulated miR‐101 in MSC‐derived exosomes was detected during osteogenic differentiation, while diminished levels of FBXW7 expression was noted. Importantly, miR‐101 was found to specifically bind to the 3′‐untranslated region of FBXW7. Meanwhile, data was obtained indicating that FBXW7 could ubiquitinate and degrade HIF1α to repress its upregulation during osteogenic differentiation. HIF1α bound to the promoter region of FOXP3 to facilitate osteogenic differentiation. Ultimately, the findings of the current study demonstrate that BMSC‐derived exosomal miR‐101 augments osteogenic differentiation in MSCs by inhibiting FBXW7 to regulate the HIF1α/FOXP3 axis. Abstract : Ultimately, the findings of the current study demonstrate that bone marrow mesenchymal stem cell‐derived exosomal microRNA‐101 (miR‐101) augments osteogenic differentiation in mesenchymal stem cells by inhibiting FBXW7 to regulate the HIF1α/FOXP3 axis.